Analysis of the Number of Leukocytes in Dengue Hemorrhagic Fever Patients at Mitra Sehat Situbondo Hospital in 2023 - Sheli Tiara Oktafiyan (LPPM Universitas dr. Soebandi, 2024)
Background: Dengue Hemorrhagic Fever is an infectious disease that still poses a significant public health challenge. Dengue fever cases in Situbondo Regency increased from 331 in 2020 to 475 in 2021 with a Case Fatality Rate (CFR) of 0.8%. Delays in diagnosing disease symptoms and lack of accurate clinical observation can be the cause of death in patients infected with dengue virus. Supporting examinations such as leukocyte count can be an accurate indicator of clinical observation. Leukocyte count in Dengue Hemorrhagic Fever patients tends to be abnormal or leukopenia. Purpose: to find out the number of leukocytes in Dengue Hemorrhagic Fever (DHF) patients at Mitra Sehat Situbondo Hospital in 2023. Methods: This study is a quantitative research using a cross-sectional study design with a retrospective approach. The research was carried out from January to April 2023. The samples used were secondary data in the form of leukocyte results taken from medical records of patients diagnosed with Dangue Hemorrhagic Fever (DHF) at Mitra Sehat Situbondo Hospital totaling 81 samples using the cohran formula technique. The data analysis technique in this study uses a descriptive approach Results: number of leukocytes <5000 was 59 respondents (72.7%), 5000-10000 was 22 respondents (27.3%), and no number of leukocytes >10000 was found Conclusions: most respondents had a leukocyte count of <5,000 cells/μL (72.75%).